Precision medicine identifies a pathogenic variant of the ITGA2B gene responsible for Glanzmann's thrombasthenia in a cat. (16th September 2020) - Li, Ronald H. L.; Ontiveros, Eric; Nguyen, Nghi; Stern, Joshua A.; Lee, Elizabeth; Hardy, Brian T.
Abstract: Background: A nonpedigreed male cat presented with epistaxis, severe bladder hemorrhage, and secondary urethral obstruction after cystocentesis. Objectives: To characterize the phenotype of a cat with bleeding diathesis and use a precision medicine approach to identify the molecular genetic defect by whole genome sequencing. Methods: Adenosine diphosphate (ADP) and arachidonic acid (AA)‐induced whole blood platelet aggregometry was performed in the affected cat and a healthy cat. Platelet activation, measured by P‐selectin expression, and surface integrin subunit β3 expression were evaluated by flow cytometry in the affected cat and healthy control. Total integrin subunit αIIb expression was assessed by western blot. Whole genome sequencing at 30× coverage was used to identify genetic variants that segregated in the affected cat compared to 194 cats from the 99 Lives Sequencing Consortium. Results: Platelet aggregometry identified significant impairment in platelet aggregation in response to ADP and AA compared to the control cat. Targeted protein expression analyses by flow cytometry and immunoblot analysis determined that the surface expression and total expression of the integrin, αIIbβ3, was absent. Whole genome sequencing identified a homozygous c.1986delC frameshift variant in the integrin subunit αIIb ( ITGA2B ) gene that was not detected in the control population. The p.Pro662fs ( ITGA2B P662X) variant terminates translation of the protein at the extracellular domain of the integrin prematurely, which is predicted to affect expression of the β3 unit. Conclusions and Clinical Importance: This novel ITGA2B variant and the associated phenotype closely resemble Glanzmann's thrombasthenia, which has never been reported in cats.